x-7-2x=12

Simple and best practice solution for x-7-2x=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-7-2x=12 equation:


Simplifying
x + -7 + -2x = 12

Reorder the terms:
-7 + x + -2x = 12

Combine like terms: x + -2x = -1x
-7 + -1x = 12

Solving
-7 + -1x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -1x = 12 + 7

Combine like terms: -7 + 7 = 0
0 + -1x = 12 + 7
-1x = 12 + 7

Combine like terms: 12 + 7 = 19
-1x = 19

Divide each side by '-1'.
x = -19

Simplifying
x = -19

See similar equations:

| -7d=50+2d | | (9x-8)+8=(3x+10)+8 | | 13x+50=-54 | | 12x-84=12x | | 3x+12=8x-8 | | 4y=y-20 | | 8v-3+3v=8 | | 0.66x-34=32 | | 87=13-2x | | -5(2x+4)=(-2-x) | | -6+11-3x=-34 | | 8a-7=4a+9 | | .5x-5=-9 | | 16+3y=22 | | 12k-3(k+5)=48 | | 8p-12q= | | 10=14+4(x-2) | | 8(x+3)+13=29 | | -(8y+5)-(-7y-7)=-3 | | -7=7(a-3) | | 5v-3(v+4)=0 | | 2y(7y+2)(8y+7)=0 | | 5(p-7)-15=3p+12 | | 65=17-14b-4b | | 4n+40=129 | | 9(2x-9)=3(6x+6) | | .5(y-10)+y=10 | | -4(4y+2)= | | x-0.30x=98 | | 3(2x-10)=6(x-5) | | 2(9s+3)=6(3s+1) | | -5b=35 |

Equations solver categories